An analysis of early career training requirements for quantity surveying professionals - Lee, Cynthia ChinTian; Perera, Srinath; Hogg, Keith (International Journal of Strategic Property Management, 2013)
Early career experience can play a significant part in lifelong professional capability and the support and knowledge gained during the early years of graduate employment can influence future career direction and success. Whilst there are prescribed models of graduate development relative to the surveying professions, for example, those relating to the APC utilised by the RICS, there has been little evaluation in terms of their relative contribution to career success. Through the use of a questionnaire survey, the issue of learning and development for new graduates in their early career, the extent to which new graduates perceive themselves to be competent in various major quantity surveying activities and, the range of graduate training provided by the employer were explored. The main conclusions drawn from the study are that: new graduates exhibit a high level of self-doubt in professional competence; task competence is influenced by frequency of application, years of postgraduate experience and the mode of study taken by graduates in entering the QS profession. There is a difference between training received by graduates working for consultant and contracting employers. Graduates from full time study mode tend to receive more training from their employers compared to part time graduates.First Publish Online: 27 Jun 2013